Only the Literal: The Contradictions of Anti-pornography Feminism - Segal, Lynne (Sexualities, 1998)
Within feminism, battles over pornography have become the wars without end. Despite the controversy it generates, the discourses of anti-pornography feminism have continued to make inroads into legal frameworks, most recently in Canada. This piece surveys the growth and questionable appeal of such feminist campaigning, under the theoretical leadership of Catharine MacKinnon: its rewriting of feminist theory; its parasitic relation to the authoritative, phallocentric discourses of gender and sexuality; its alliance with the most reductive, behaviouristic psychology; its disavowel of fantasy and psychic life; its provocative mirroring of both the style and content of the `pornography' it deplores; its unwavering pursuit of legal remedies which enhance the power of state regulation of sexuality; its threat to subversive expressions of women's sexual agency and repudiation of any possibilities for sexual resignifications.
Keywords: cours; discipline; droits des femmes*; histoire et politique; militance; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Fantasies of femininity: Reframing the boundaries of sex - Ussher, Jane M. (Rutgers University Press, 1997)
In Fantasies of Femininity, Jane Ussher focuses on unraveling the contradictory visions of feminine sexuality: the fact that representations of the definition of woman seethe with sexuality yet for centuries women have been condemned for exploring their own sexual desires. In her quest for the sources of feminine representation, Ussher interviewed dozens of women - as well as some men - and combed popular media - from Seventeen to Cosmopolitan and Dallas to Donahue - to identify what shapes women's symbolic images of sex and femininity. Ussher argues that women have effectively resisted and subverted these archetypal fantasies of femininity, and in the process of so doing, reframed the very boundaries of sex. In this way, she exposes as myth much of what we think we know about "woman" and about "sex."
Keywords: approches et analyses; cours; discipline; fem1000; inégalités; premier cycle; psychologie; sciences humaines; sexualité; sexualité féminine; stéréotypes; systèmes d'oppressions; thématiques; études culturelles

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Les éditions du remue-ménage, 1983)
Les textes Morgan, R. (1983). La pornographie et le viol : théorie et pratique et Dworkin, A. (1983). Pour les hommes, liberté d’expression. Pour les femmes, silence, s’il vous plaît ont été donné en lecture au corus SEX1911.
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Ce sexe qui n'en est pas un - Irigaray, Luce (Les Éditions de Minuit, 1977)
Comment parler de l’autre côté, se demanda Alice. Car, en fait de merveilles, elle avait découvert qu’elle était plus d’une, et qu’une seule langue ne pouvait signifier ce qui avait lieu entre elles. Il fallait pourtant essayer de se faire entendre. Alors, s’appliquant, elle reprit : Que dire d’une sexualité féminine autre ? Autre que celle prescrite dans et par l’économie du pouvoir phallique. Autre que celle encore et toujours décrite – et normalisée – par la psychanalyse. Comment inventer, ou retrouver, son langage ? Comment interpréter le fonctionnement social à partir de l’exploitation des corps sexués des femmes ? Que peut être, dès lors, leur action par rapport au politique? Doivent-elles ou non intervenir dans les institutions ? Par quel biais échapper à la culture patriarcale ? Quelles questions poser à son discours ? À ses théories ? À ses sciences ? Comment les énoncer pour qu’elles ne soient pas, à nouveau, soumises à la censure ou au refoulement ? Mais aussi : comment déjà parler femme ? En retraversant le discours dominant. En interrogeant la maîtrise des hommes. En parlant aux femmes, entre femmes. Questions – parmi d’autres – qui s’interrogent et se répondent dans plusieurs langues, sur plusieurs tons, à plusieurs voix. Déconcertant l’uniformité d’un discours, la monotonie d’un genre, l’autocratie d’un sexe. Innombrables les désirs des femmes, et jamais réductibles à l’un ni à son multiple. Le jour était déjà levé depuis longtemps. Une histoire n’en finissait pas d’imposer son ordre. De l’obliger à s’exposer dans une clarté un peu froide. Dans l’attente d’un autre matin, elle repassa derrière le miroir, et elle se retrouva entre elles toute(s). Luce Irigaray
http://catalogue.bnf.fr/ark:/12148/cb345889016
Keywords: 1900-1999; 1970-1979; corps; cours; cycles supérieurs; différence des sexes; discipline; europe; fem1000; fem7000; france; har4600; langage féminin; lit3220; premier cycle; psy4910; psychanalyse; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualité féminine; thématiques; écriture des femmes*